1993
DOI: 10.1080/00288233.1993.10427495
|View full text |Cite
|
Sign up to set email alerts
|

Collagen in two muscles of sheep selected for weight as yearlings

Abstract: Collagen concentration and solubility were examined in the semimembranosus and biceps femoris muscles of Romney lambs from the Hight line, a line selected for nine generations on the basis of high body weight at 1 year old. Lambs from the Control (CON) and high body weight (HBW) lines were slaughtered at five ages (0, 42, 70, 274, 365 days). In the semimembranosus muscle, there was no evidence of concentration or solubility differences between the lines at any age, but there was a subtle sex by age interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Collagen alpha-3 (VI) chain is a stromal protein in connective tissue, which is the only protein that had greater abundance in loins from wether lambs than ewe lambs in the current study. Similar results were reported by Monteschio et al [32] where both soluble collagen and total collagen content were greater in loins from wether lambs than ewe lambs, likely due to the increased collagen synthesis in males at puberty [33]. Hopkins et al [34] reported that measurement of collagen concentration did not explain the variation in shear force and sensory tenderness observed in the meat from lambs.…”
Section: Proteome Abundance Differences Due To Gender (Chic-e Vs Chic-w)supporting
confidence: 75%
“…Collagen alpha-3 (VI) chain is a stromal protein in connective tissue, which is the only protein that had greater abundance in loins from wether lambs than ewe lambs in the current study. Similar results were reported by Monteschio et al [32] where both soluble collagen and total collagen content were greater in loins from wether lambs than ewe lambs, likely due to the increased collagen synthesis in males at puberty [33]. Hopkins et al [34] reported that measurement of collagen concentration did not explain the variation in shear force and sensory tenderness observed in the meat from lambs.…”
Section: Proteome Abundance Differences Due To Gender (Chic-e Vs Chic-w)supporting
confidence: 75%
“…In the particular case of the milk-fed lambs (types 4 and 7), the high muscle collagen content could also have been a consequence of their early stage of development. In sheep, Young et al (1993a) found that muscle collagen content was maximal at birth, was then reduced by half within 1.5 months of age and then remained stable at older ages up to one year. A similar shift has also been observed in cattle between birth and the age of 8 months onwards (Boccard et al 1979).…”
Section: Comparison Of Lamb Typesmentioning
confidence: 99%
“…Usually breed effects can be explained by differences in maturity at slaughter and the consequent stage of fat tissue development (Vesely and Peters 1966;Bray 1988;Dransfield et al 1990;Dufey and Wirz 1995a;SaAudo et al 1998). As animal age increases, lamb meat exhibits a more intense color, lower tenderness and a stronger flavor (Jeremiah et al 1971;Bruwer et al 1987;Bray 1988;SchUnfeldt et al 1993;Young et al 1993a). Both feeding level and type of feed influence the amount and the composition of lamb tissue lipids, and consequently meat flavor (Sink and Caporaso 1977;Young et al 1998;Fisher et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Jeremiah et al (1998), for example, concluded that sensory tenderness scores declined and WB shear values increased with increasing lamb age up to 15 months. Other studies have also indicated that the tenderness of lamb may decrease within the first 15 months (Jeremiah et al 1971;Purchas et al 1979;Devine et al 1993;Young et al 1993b;Carson et al 1999) Further research needs to be done using a range of muscles and cooking conditions to determine whether it would be commercially advantageous to subdivide lamb into age classes if the classes could be shown to differ in palatability characteristics such as tenderness.…”
Section: Breed and Age Effects On Meat Qualitymentioning
confidence: 99%